Nasikh Wa Al-Mansukh Dan Korelasinya Dengan Al-Qur’an - Lena Ishelmiani Ziarahah; I. Nurul Aen; Syahrul Anwar (STAI Siliwangi Bandung, 2023)
Abstract: This study aims to analyze two different sides of views about the Qur'an, where the Qur'an is a book for Muslims in which there is no dispute (ikhtilaf), while on the other hand there is a Qur'anic verse that recites the pronunciation of nasakh as found in Q.S. al-Baqarah verse 106. This research uses a qualitative approach with a descriptive method. The results showed that there are different points of view of the scholars, namely: First, those who accept at once and give support to nasakh which means in the Qur'an there is cancellation. These scholars include Ibn Kasir and Ahmad Mustafa al-Maragi. Second, they do not accept nasakh in the sense of nullifying the law that Allah directly revealed and they interpret as nasakh equals takhsis or more to specification. These scholars include 'Abd al-Muta'al al-Jabri and Muhammad al-Bahi. So it is not surprising that the discussion related to Nasikh Wa al-Mansukh is an interesting topic to be studied. Abstrak: Penelitian ini bertujuan untuk menganalisis dua sisi pandangan berbeda tentang al-Qur’an, di mana al-Qur’an merupakan kitab bagi umat Islam yang di dalamnya tidak ada perselisihan (ikhtilaf), sedangkan di sisi lain terdapat ayat al-Qur’an yang melafadzkan lafal nasakh sebagaimana terdapat pada Q.S. al-Baqarah ayat 106. Penelitian ini menggunakan pendekatan kualitatif dengan metode deskriptif. Hasil penelitian menunjukkan bahwa terdapat perbedaan sudut pandang para ulama, yaitu: Pertama, mereka yang menerima sekaligus dan memberi dukungan atas nasakh yang berarti dalam al-Qur’an terdapat pembatalan. Ulama tersebut di antaranya ialah Ibnu Kasir dan Ahmad Mustafa al-Maragi. Kedua, mereka tidak menerima nasakh dalam artian pembatalan hukum yang secara langsung Allah turunkan dan mereka artikan sebagai nasakh sama dengan takhsis atau lebih ke pengkhususan. Ulama tersebut di antaranya ‘Abd al-Muta’al al-Jabri juga Muhammad al-Bahi. Maka tidak heran apabila pembahasan terkait Nasikh Wa al-Mansukh merupakan topik yang menarik untuk ditelaah.